GAMBARAN RESPON HOSPITALISASI PADA ANAK USIA PRASEKOLAH YANG PERTAMA KALI DIRAWAT INAP DI RUMAH SAKIT - Fiteli, Imeilda (Jurnal Keperawatan Profesional, 2024)
Hospitalization causes the child to temporarily separate from their parents, which can lead to excessive fear, worry, and anxiety. The negative responses that arise in children during hospitalization can disrupt the care process and create new challenges in various aspects of the child's development in the future. The research aims to determine the overview of the responses of children who are hospitalized for the first time. Methods: The research is a quantitative study using a descriptive approach with a sample size of 30 preschool-aged children. Sample data is collected through a questionnaire prepared by the researcher using the accidental sampling technique. The data is analyzed using univariate analysis. Results: The most common age of the respondents is 4 and 5 years old (30%), the majority of the respondents are female (60%), respondents have siblings (76.7%), some respondents had a short hospital stay (50%), and most of the respondents were cared for by their mothers during hospitalization (90%). Children's responses to hospitalization include anxiety about separation (76.7%), a sense of loss of control (70%), and fear of injury and pain (83.3%). Conclusion: Hospitalization in preschool-aged children includes anxiety about separation, a sense of loss of control, and fear of bodily injury and pain. Nurses should communicate with the family and child using simple explanations, offering choices, and using visual aids to explain hospital procedures.